2013
DOI: 10.1111/zph.12085
|View full text |Cite
|
Sign up to set email alerts
|

The Limitations of Pulsed‐Field Gel Electrophoresis for Analysis of Yersinia enterocolitica Isolates

Abstract: This study describes the analysis of 432 isolates of Yersinia enterocolitica by pulsed-field gel electrophoresis (PFGE). PFGE had a high level of discrimination with biotype 1A isolates (Simpson's Diversity Index 0.997), but with the clinically important biotypes 2, 3 and 4, the discriminatory ability of PFGE was so low as to severely limit its usefulness (DI <0.6). For biotypes 2, 3 and 4, 79% or more of isolates of each biotype were of just three different PFGE profiles. Because of this, four known outbreaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
5
18
1
Order By: Relevance
“…Although the number of biotype 2 strains was 46 and closer to our sampling, the discrimination index was 0·319 considering just strains of this biotype (Gilpin et al . ) and in this present study the discrimination index was 0·965 (data not shown). In this way, we may conclude that the use of Xba I in PFGE is more suitable to genotype and differentiate Y .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although the number of biotype 2 strains was 46 and closer to our sampling, the discrimination index was 0·319 considering just strains of this biotype (Gilpin et al . ) and in this present study the discrimination index was 0·965 (data not shown). In this way, we may conclude that the use of Xba I in PFGE is more suitable to genotype and differentiate Y .…”
Section: Discussionsupporting
confidence: 52%
“…Also, Gilpin et al . () used the restriction enzymes Apa I and Not I. Although the number of biotype 2 strains was 46 and closer to our sampling, the discrimination index was 0·319 considering just strains of this biotype (Gilpin et al .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…enterocolitica [49], the strains were then subjected to MLVA, which has a higher discriminatory power [36,37]. This MLVA analysis based on six loci also gave a unique pattern (7-8-7-8-8-2) for the 14 Y .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies, for example, have used NotI and XbaI as restriction enzymes (Bonardi et al, ; Falcão, Falcão, Pitondo‐Silva, Malaspina, & Brocchi, ; Fredriksson‐Ahomaa, Stolle, & Stephan, ). However, limited diversity among biotypes 4 and 3 was observed at pig slaughterhouse level even between strains of different geographical origins, like Germany, Finland, New Zealand, and China (Fredriksson‐Ahomaa et al, ; Gilpin et al, ; Liang et al, ). Another increasingly popular technique used to type Y. enterocolitica is the Multi‐locus variable number tandem repeat analysis (MLVA).…”
Section: Introductionmentioning
confidence: 99%